Pelatihan Perencanaan Keuangan Syariah Bebas Pinjol Untuk Penguatan Ekonomi Keluarga Muslim - Ahmad Dahlan Malik; Ahmad Hudaifah; Mella Agustina; Safaatul Udmah (FEB-UP Press, 2025)
The emergence of online loan problems and weak knowledge, literacy, understanding and Sharia-based personal and family financial management cause family disharmony. Therefore, the purpose of this community service is to provide an understanding of Sharia financial planning free of online loans through a community-based participatory research method for Aisyiyah administrators in Gresik region with a training, socialization and mentoring approach. The results of the activity showed an increase in participants' understanding of Shariah financial planning and pinjol-free family financial management, both anticipatory and pinjol-free.